GÁS NATURAL: POTENCIALIDADES DE UTILIZAÇÃO NO BRASIL - Fioreze, Mariele; Hedlund, Keila Fernanda Soares; Graepin, Cristiane; Silva, Tainara Casa Nova; Azevedo, Francéllwika Catharine Gomes de; Kemerich, Pedro Daniel da Cunha (Revista Eletrônica em Gestão, Educação e Tecnologia Ambiental, 2013)
http://dx.doi.org/10.5902/223611707896 The market for natural gas for electric power generation has increased considerably in Brazil, supported by the environmental and technological advantages of this energy. Despite the historical records that indicate that natural gas was already being used in Iran between 6000 and 2000 B.C, this was only introduced in the European market in 1659, and still later, began to be used in Brazil, only around 1940 due to oil and gas discoveries in Bahia. Currently, this energy is gaining more space, mainly due to environmental requirements, the construction of the Bolivia-Brazil pipeline and the discoveries of Pre-Salt layer in the Santos Basin. Similarly to oil, the natural gas has its training associated with decomposition of plants and animals in an environment with low oxygen conditions and high temperature and pressure. It’s a combination of light hydrocarbons and gases, particularly methane, and has lower environmental impact than oil and coal. It is considered as a transition fuel, and their use until needed to develop alternativetechnologies with low environmental impact for the power supply.